Development And Analysis Of High Altitude Balloon Performance Calculator - Jamaludin, Haikal (Universiti Sains Malaysia, 2021)
A high altitude balloon is an unmanned balloon that is loaded with gases that lift more than air and is released into the upper atmosphere for any scientific endeavor. It is difficult to calculate the LTA gas performance in order to select the best balloon performance, and a calculator is required to predict the balloon performance prior to launching the high altitude balloon, as both of these topics will be covered in this paper. This project's technique began with research on the HAB and LTA gases. The technical specification data will be obtained from the manufacturer in order to determine the parameters for the HAB's performance. Using the parameters gathered from the implemented computation, a graphical user interface will be developed. The results will then be compared among the manufacturers using the GUI. The interface for the calculator, as well as a comparison of the HAB performance, will be displayed in the results. Because the lift produced by Hydrogen gas is more than that produced by Helium gas, the ascension rate of Hydrogen gas is greater than that of Helium gas. As the launch volume grew, the ascension rate increased due to more lift produced on the balloon with higher volume upon release. Because the pressure within the balloon is greater on the balloon with more capacity at release as it expands quicker, the burst height will drop as the launch volume increases. The descent rate of a parachute with a bigger payload will be quicker than for a lighter payload due to the increased drag produced by the payload, and the descent rate at higher altitude will be faster due to the lower density at higher altitude. Finally, the LTA gases may be distinguished using the GUI. We were also able to investigate the MATLAB program and create a graphical user interface for the balloon performance. Finally, the HAB performance may be predicted utilizing the GUI development.